Current Issues Concerning the Epidemiology of Acquired Immunodeficiency Syndrome and Human Immunodeficiency Virus - Lipson, Alan R. (1992)
This discussion was selected from the weekly staff conferences in the Department of Medicine, University of California, San Francisco. Taken from a transcription, it has been edited by Nathan M. Bass, MD, PhD, Associate Professor of Medicine, under the direction of Lloyd H. Smith Jr, MD, Professor of Medicine and Associate Dean in the School of Medicine.